Disputable issues regarding the systematisation of bylaws and regulations - M. Yu. Burdin; I. L. Nevzorov; Yu. O. Bezusa (Law and Safety)
The article deals with the issue of systematisation of by-laws and regulations resulting from the adoption of the Law of Ukraine “On Lawmaking”.